Indigenous Knowledge Systems in Sub-Saharan Africa : An Overview - Donnelly-Roark, Paula (World Bank, Washington, DC, 2012)
Recent reports document that the failure of projects in Africa over the past twenty years happened because local people's involvement and control were thought to be part of the goal of development, rather than the process of development. Many people and groups throughout Africa strongly believe that positive new development can happen, but only if the people themselves stay in control of their resources, economies, and culture. This capacity for local control only happens, however, when people are allowed to internally work from, expand, and change their own institutions and knowledge systems. Thus, the opportunities surrounding initiatives to bring together indigenous knowledge systems and natural resource conservation are immense - however, so are the dangers. It is the intent of this article to briefly define some of the dangers so that they may be avoided, and define some of the opportunities so that they may be more thoroughly and solidly developed. To accomplish this, the article briefly outlines some issues which seem to contain strong elements of both danger and opportunity.